L'affaire des « champignons magiques » - Manganas, Antoine (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
Following a number of acquittals based on a strict interpretation of the terms of the Food and Drugs Act, the Supreme Court of Canada recently had to determine, in Dunn, if a mushroom containing « psilocybin » was a restricted drug despite the fact that the legislation was referring only to the chemical substance and not to the plant itself The Supreme Court found that the text was clear and that the fact that « psilocybin » may be contained within a mushroom does not destroy its character as a restricted drug. Drug traffic must naturally be condemned, but that is not the problem for the moment. The problem is that the Supreme Court of Canada adopted, in Dunn, the rule of the liberal interpretation of a penal statute despite the fact that, not so long ago, it chose a different approach when dealing with a different statute. We are critical of both the way the inferior courts treated the cases before them and the way the legislator treated the problem. We think that it was possible for the lower courts to find the accused guilty of attempting to commit the offense. We think also that it was possible for the legislator to anticipate those situations and take some precautions by deliberately adopting a text capable of embracing these cases.